Analysis of the performance ratio of a photovoltaic power plant according to development and operation - Silva, Ronny Dias Renke Brandão e (2020)
Photovoltaic plants are also evaluated according to their Performance Ratio. This indicator allows to compare solar plants, regardless of their location or capacity, and may vary between positive or negative values due to several factors. Based on the knowledge gained by the author during the curricular internship at IBC Solar Energy GmbH, this document shows the electrical calculations and energy losses involved during project development, and then analyses the development and operation of sixteen photovoltaic plants, seeking to determine, through a case study, the main factors that negatively impact the efficiency. Based on this study, the author shows a software he developed, that was designed to increase reliability and decrease time spent during Performance Ratio calculations.